2016
DOI: 10.1002/cphc.201501067
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Excess Sensitivity to Below One Percent by Using Femtosecond Photoelectron Circular Dichroism

Abstract: Photoelectron circular dichroism (PECD) is experimentally investigated with chiral specimens with varying amounts of enantiomeric excess (ee). As a prototype, we measure and analyze the photoelectron angular distribution from randomly oriented fenchone molecules in the gas phase that result from ionization with circularly polarized femtosecond laser pulses. The quantification of these measurements shows a linear dependence with respect to the ee values. In addition, differences in the ee values (denoted as det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 26 publications
(41 reference statements)
0
103
0
2
Order By: Relevance
“…In a more extensive study using REMPI--PECD Lux et al 52 have similarly demonstrated relative e.e. determinations with better than 1% uncertainty for fenchone mixtures spanning the full range (0-100 %).…”
Section: Fenchone Datamentioning
confidence: 85%
“…In a more extensive study using REMPI--PECD Lux et al 52 have similarly demonstrated relative e.e. determinations with better than 1% uncertainty for fenchone mixtures spanning the full range (0-100 %).…”
Section: Fenchone Datamentioning
confidence: 85%
“…Such developments are now attracting considerable interest because of the possibilities for time-resolved chiral probing, and convenient lab-based analytical applications that are thereby opened up. [23][24][25] In particular, the use of resonantly enhanced multiphoton ionization (REMPI), as opposed to single VUV photon ionization, creates new opportunities for increased vibrational selectivity in PECD, as ionization then occurs out of a prepared vibrational level or wavepacket. [26] Besides permitting greater control of vibrational excitation and mode specificity, REMPI brings with it opportunities for selective isomer and/or conformer specific ionization.…”
Section: Introductionmentioning
confidence: 99%
“…data has reached the 1% accuracy level. 15,16 So far, little has been reported regarding the effect of laser wavelength on the measured PECD asymmetry in multiphoton excitation. Lehmann et al 8 reported multi photon-(MP-) PECD data for laser excitation at 400 and 380 nm in camphor.…”
Section: Introductionmentioning
confidence: 99%